2008
DOI: 10.1111/j.1365-2966.2008.12907.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic giant branch stars in the Phoenix dwarf galaxy

Abstract: JHK s near‐infrared photometry of stars in the Phoenix dwarf galaxy is presented and discussed. Combining these data with the optical photometry of Massey et al. allows a rather clean separation of field stars from Phoenix members. The discovery of a Mira variable (P= 425 d), which is almost certainly a carbon star, leads to an estimate of the distance modulus of 23.10 ± 0.18 that is consistent with other estimates and indicates the existence of a significant population of age ∼2 Gyr. The two carbon stars of D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…other recent near-IR studies, e.g., Gullieuszik et al 2007a,b;Menzies et al 2008). It is tempting Fig.…”
Section: The Evolved Stellar Populations Of Uks 2323-326mentioning
confidence: 67%
“…other recent near-IR studies, e.g., Gullieuszik et al 2007a,b;Menzies et al 2008). It is tempting Fig.…”
Section: The Evolved Stellar Populations Of Uks 2323-326mentioning
confidence: 67%
“…These additional targets were selected among the brightest sources in the [3.6] band, but quite often they were fainter than the magnitude cutoff criteria (M 3.6 μm ≤ −9 mag), and they did not always satisfy our selection criteria in terms of the [3.6]-[4.5] color. Moreover, 10 of these additional targets have been reported as candidate carbon stars based on their photometry (Battinelli & Demers 2000, 2004Menzies et al 2008). In total, 79 stars were observed in four dIrr galaxies: 19 in Pegasus, 14 in Phoenix, 15 in Sextans A, and 31 in WLM.…”
Section: Target Selectionmentioning
confidence: 99%
“…Although some candidates were listed in the literature as candidates for carbon stars (Battinelli & Demers 2000, 2004Menzies et al 2008), we still observed them to fill the free space on MXU masks. In total we observed ten photometric candidates, eight of which are spectroscopically confirmed as carbon stars in this work and are presented in Fig.…”
Section: Carbon Starsmentioning
confidence: 99%
“…There is, however, a very clear tail of longer period stars representing a small younger population. These are missing from the dwarf spheroidals (Menzies et al 2008;2010;Whitelock et al 2009), as might be expected given their commonly accepted star formation histories (although note that the total number of stars in the dwarf spheroidals is much smaller than in NGC 6822). Fig.…”
Section: Agb Variables In Ngc 6822mentioning
confidence: 89%
“…The observations discussed here form part of a study of AGB stars in Local Group galaxies and detailed analysis have been published for the Phoenix, Leo I and Fornax dwarf spheroidals by Menzies et al (2008Menzies et al ( , 2010 and Whitelock et al (2009). A preliminary study of the variables in NGC 6822 was made by Nsengiyumva (2010) for his MSc thesis, but the detailed analysis is still underway, and this account highlights only a few preliminary findings.…”
Section: Introductionmentioning
confidence: 99%